Ultrafast conformational dynamics of Rydberg-excited N-methyl piperidine. Issue 48 (3rd December 2021) - Du, Wenpeng; Gao, Yan; Stankus, Brian; Xu, Xuan; Yong, Haiwang; Weber, Peter M.
Abstract : Ultrafast coherent oscillations and subsequent conformational dynamics in N -methyl piperidine are observed upon excitation to 3s and 3p Rydberg states. Abstract : We have observed the ultrafast conformational dynamics of electronically excited N -methyl piperidine (NMP) using time-resolved Rydberg fingerprint spectroscopy. Optical excitation at various wavelengths ranging from 212 nm to 229 nm leads to the 3s or 3p Rydberg states and induces coherent oscillatory motions with periods of about 700 fs. These coherent motions survive the internal conversion from 3p to 3s but then dephase on a time scale of a few oscillations. Intramolecular vibrational energy redistribution on a picosecond time scale leads to an equilibrium between two conformeric structures that are separated in binding energy by 0.09 eV. Model calculations using the DFT-SIC method are in excellent agreement with the experiments and identify the conformers as the chair and twist structures of NMP. The analysis of the equilibrium parameters at long time delays as a function of excitation wavelength allows for the extraction of thermodynamic parameters for the conformeric transformation. We derive an enthalpy of the chair to twist reaction in the 3s excited state of 62 meV with an entropy of 19.70 J mol −1 K −1 . An activation energy of 276 meV is also obtained with a kinetic model.